Whistleblowers : Broken Lives and Organizational Power - Alford, C. Fred (Book collections on Project MUSE., 2001)
"In a dark departure from our standard picture of whistleblowers, C. Fred Alford offers a chilling account of the world of people who have come forward to protest organizational malfeasance in government agencies and in the private sector. The conventional story - high-minded individual fights soulless organization, is persecuted, yet triumphs in the end - is seductive and pervasive. In speaking with whistleblowers and their families, lawyers, and therapists, Alford discovers that the reality of whistleblowing is grim. Few whistleblowers succeed in effecting change; even fewer are regarded as heroes or martyrs."--Jacket